2001
DOI: 10.1021/bi0014195
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Specificity of the Integral Membrane Protease OmpT Determined by Spatially Addressed Peptide Libraries

Abstract: Escherichia coli outer membrane protease T (OmpT) is an endopeptidase that specifically cleaves between two consecutive basic residues. In this study we have investigated the substrate specificity of OmpT using spatially addressed SPOT peptide libraries. The peptide acetyl-Dap(dnp)-Ala-Arg/Arg-Ala-Lys(Abz)-Gly was synthesized directly onto cellulose membrane. The peptide contained the aminobenzoyl (Abz) fluorophore, which was internally quenched by the dinitrophenyl (dnp) moiety. Treatment of the SPOT membrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
80
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(92 citation statements)
references
References 27 publications
12
80
0
Order By: Relevance
“…This result was in accord with the previous belief that OmpT protease is an outer-membrane protease. [19][20][21] At the same time, it was clearly seen that the supernatant contained a substantial amount OmpT protease. To further confirm the intactness of OmpT protease induced by plasmid pOmpT-Tet, we examined OmpT protease activity.…”
Section: Effect Of Ompt Protease On Formation Of Protein Polymers Conmentioning
confidence: 82%
See 1 more Smart Citation
“…This result was in accord with the previous belief that OmpT protease is an outer-membrane protease. [19][20][21] At the same time, it was clearly seen that the supernatant contained a substantial amount OmpT protease. To further confirm the intactness of OmpT protease induced by plasmid pOmpT-Tet, we examined OmpT protease activity.…”
Section: Effect Of Ompt Protease On Formation Of Protein Polymers Conmentioning
confidence: 82%
“…It is well-established that OmpT protease specifically cleaves between two consecutive basic residues. 13,21,22) Taking this into account, we examined the amino acid sequence of Sup35NM and found that it had no arginine (R), and that it had four pairs of lysine (K) in the M domain (Fig. 6B).…”
Section: Possible Cleavage Sites Of Ompt Protese In Sup35nmmentioning
confidence: 99%
“…This specificity could not be due to different active sites on Pla, since a substitution mutation inactivating the enzymatic site of Pla for plasminogen cleavage also affected the inactivation of LL-37 or CRAMP. OmpT and PgtE cleave preferentially between two basic amino acid residues (14,17), explaining why CAMPs such as cathelicidins, with their repeated pairs of Arg and/or Lys residues, are optimal targets for these omptins (24,59). The efficiency (k cat /K m ) of OmpT for a peptide with an Arg2Arg cleavage site was fourfold better than that for a similar peptide with an Arg2Val cleavage site (42,65).…”
Section: Discussionmentioning
confidence: 99%
“…3) [21], resulted in at least sevenfold lower activity. OmpT preferentially cleaves peptides between two basic amino acids [5], therefore the anionic nature of the cleft is probably a major determinant of its substrate speci¢city. More speci¢cally, we proposed earlier, based on the crystal structure of OmpT [21], that Glu 27 and Asp 208 may de¢ne the high speci¢city of OmpT for Arg or Lys at position P1 in the substrate (nomenclature as in reference [27]).…”
Section: Discussionmentioning
confidence: 99%